The value of routine portable chest radiograph of patients in intensive care unit (ICU) - Hamzah, Ahmad (2008)
The value of routine portable chest radiograph of patients in Intensive Care Unit (ICU). Introduction: Since the advent of ICU set up, there has been two schools of thought regarding the usage of routine portable chest radiograph in critically ill patients. One school of thought says that routine portable CXR will give a significant nwnber of unsuspected findings while the other claimed that it just increased radiation dose to the patient and little benefits obtained. At present, two standards of care have evolved, one using routine CXR and the other using clinically indicated CXR.. In Hospital Universiti Sains Malaysia (HUSM), some of our ICU physicians practised routine CXR particularly in cardiopulmonary disease with some modification while some of them requested CXR when clinically indicated. Our study aim is to detennine the diagnostic and therapeutic efficacy of routine chest radiographs in ICU HUSM xiii Methodology: This study was a cross sectional design conducted in HUSM starting from October 2006 till March 2007. 1016 CXRs were obtained within the study period and 501 portable CXRs were included in this study. The CXR were analysed and divided into routine and non routine groups. The CXR findings were recorded. The images were reviewed by a trainee radiologist using GE Pathspeed Diagnostic Workstation in the department of radiology. Approval from the Research Board Committee was obtained prior to study. Results: Fifty five (17.3 %) CXR.s showed new lesions or significant abnonnality in routine group, compared with 132 (72.1 %). There was a significant difference of detecting new lesion between routine and non routine with p value of 0.001. The CXR with new findings that resulted in an intervention was significantly higher in non routine compared to the routine groups, 68.9% and 9.4% respectively with p value ofO.OOl. XIV Conclusion: The non routine protocol yielded better diagnostic and therapeutic efficacy than routine CXR. The use of routine CXR is not cost effective. It resulted in an increased radiation dose to the patient with only little benefits.